Association between clinical and genetic diagnosis in patients with LQT syndrome: importance of genetic testing - Dionisio, Leonardo Raul (2019)
Long QT syndrome (LQTS) is a congenital genetic disorder that cause cardiac arrhythmia and sudden death. The genes more frequently implicated are those encoding for the K+ channels KCNQ1 (40 - 45 %) and HERG (40 – 45 %), and the Na+ channel Nav1.5 (5 – 8 %). Dysfunction in these channels leads to QT interval lengthening in ECG. Molecular identification of the causes of this disease contributes to better diagnosis, risk stratification and pharmacological treatment improvement. Our aim is to correlate clinical diagnosis with genetic variants of LQTS. We examined the LQT-associated genes KCNQ1, KCNH2 and SCN5A using gDNA extracted from 6 subjects. Five of them showed a prolonged QT interval on the ECG (>460 ms) while 1 first-degree relative presented a normal QT interval (<450 ms). The group (3 males and 3 females, 0-62 years old) included 1 with sudden cardiac death history under 40 years old and 1 with presyncope and documented polymorphic ventricular tachycardia. We amplified all exons from the 3 genes by PCR followed by sequencing. For KCNQ1 we found the uncommon variant c.1638G>A (p.Ser546=) in 2 subjects. In 1 patient we could not amplify exon 16, suggesting exon deletion. For KCNH2 we found the following variants: c.1692A>G (p.Leu564=) in 1 patient, c.1956T>C (p.Tyr652=) in 5 out of 6 cases and c.2690A>C (p.Lys897Thr) in 1 patient. Finally, we found the likely-pathogenic variant c.982C>T (p.Arg328Cys). For SCN5A no variants were detected at the tested exons. We found benign and pathological genetic variants in either KCNQ1 or KCNH2 genes of our population. No information about the exon 16 deletion for KCNQ1 as a pathological variant has been reported. To our knowledge, this is the first genetic test of LQTS performed in Argentina. Genetic characterization will impact on patient habits, avoiding risk situations such as sports, acute stress or cardiotoxic drugs therapies. Moreover, these studies will enable to set patient-oriented pharmacological treatments.